Multifactorial regulators of tumor programmed death-ligand 1 (PD-L1) response - Dorand, R. Dixon; Petrosiute, Agne; Huang, Alex Y. (Translational Cancer Research, 2017)
Tumor cells hijack physiological mechanisms to create favorable conditions that allow them to survive and thrive within the hostile tissue and immune microenvironments. The identification and subsequent therapeutic blockade against immune checkpoint molecules including cytotoxic T lymphocyte associated antigen 4 (CTLA-4; CD152), programmed cell death protein 1 (PD-1; CD279) and its ligand programmed death-ligand 1 (PD-L1; CD274; B7-H1) have evoked much excitement in cancer immunotherapy against a variety of chemo-refractory cancers (1-4). Since the initial characterization of the PD-1/PD-L1 axis over 2 decades ago (5-7), over 4,000 articles have been published exploring how this immune checkpoint receptor-ligand pair influence tumor development, survival, and metastasis (2,8). Surprisingly, however, only a handful of studies have described how tumor PD-L1 is regulated at the transcriptional and post-translational levels. Recent studies by Mezzadra et al. (9). and Burr et al. (10) describe a novel post-translational mechanism by which PD-L1 is regulated within primary human dendritic cells and a variety of human tumor cell types, adding to our understanding of how this critical immune regulatory axis is regulated.